2012 19th IEEE International Conference on Electronics, Circuits, and Systems (ICECS 2012) 2012
DOI: 10.1109/icecs.2012.6463759
|View full text |Cite
|
Sign up to set email alerts
|

FPGA-based autonomous parking of a car-like robot using Fuzzy Logic Control

Abstract: This paper proposes a hardware solution to the problem of autonomous parking of a car-like robot. The proposed system scans for a valid parking space and performs the necessary manoeuvres to park the robot within that space. Parallel and perpendicular parking is achieved by using a fuzzy logic based system that was developed in a simulation environment and subsequently prototyped on a custom built, car-like robot. Fuzzy logic is being proposed as it provides a fast response with a very small hardware footprint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Scicluna et al 10 suggested a hardware solution to the autonomous parking problem of a car-like robot. They designed a Fuzzy Logic Controller for parallel and vertical parking.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Scicluna et al 10 suggested a hardware solution to the autonomous parking problem of a car-like robot. They designed a Fuzzy Logic Controller for parallel and vertical parking.…”
Section: Related Workmentioning
confidence: 99%
“…They designed a Fuzzy Logic Controller for parallel and vertical parking. The main difference of our study with the work by Scicluna et al 10 is that we utilized a solution based on ANNs which are specifically trained for self-parking tasks.…”
Section: Related Workmentioning
confidence: 99%
“…Penelitian menggunakan CLMR telah banyak dilakukan oleh beberapa peneliti seperti pada (Baturone et al 2004;Chiu et al 2005;El-Khatib & Hamilton, 2006;Gucrrcro et al 2014;Liu et al 2011;Ouadah et al 2006;Scicluna et al 2012;Abatari et al 2013). Pada makalah ini memaparkan suatu implementasi CLMR dengan Ackerman steering pada sistem robot penjejak garis.…”
Section: Pendahuluanunclassified
“…This parking operation is useful for parallel parking operation. [7] In 2012, N.Scicluna,E.Gatt,O.Casha,I.Grech,andJ.Micallef proposed a paper for autonomous parking using fuzzy logic control in International conference named "Fpga-based autonomous parking of a car-like robot using fuzzy logic control" [8] After having knowledge about these algorithms, generally systems need parking space more than 1.4 times of the vehicle length for the parking process. [9] …”
Section: Previous Parking Algorithmsmentioning
confidence: 99%